2015
DOI: 10.1016/j.wem.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Coca: High Altitude Remedy of the Ancient Incas

Abstract: The use of coca leaf for medicinal purposes is a centuries-old tradition of the native peoples of South America. Coca products are thought by many laypersons to provide risk-free benefits to users participating in strenuous activities at high altitude. Physiologic studies of coca have increased understanding of its possible mechanism of action as well as its potential impact on high altitude activities. This present work explores the role of coca throughout the history of the Andean peoples and explores whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Overall, coca’s physical performance effects are relatively mild, but potentially clinically significant. Biondich and Joslin (2015) [98] and Biondich and Joslin (2016) [79] indicated that coca’s impact on glucose availability appears to be coca’s most scientifically-validated metabolic effect [93]. They reported the value of using coca in reducing the symptoms of altitude sickness.…”
Section: Erythroxylum Coca and E Novogranatense: Coca’s Productivmentioning
confidence: 99%
“…Overall, coca’s physical performance effects are relatively mild, but potentially clinically significant. Biondich and Joslin (2015) [98] and Biondich and Joslin (2016) [79] indicated that coca’s impact on glucose availability appears to be coca’s most scientifically-validated metabolic effect [93]. They reported the value of using coca in reducing the symptoms of altitude sickness.…”
Section: Erythroxylum Coca and E Novogranatense: Coca’s Productivmentioning
confidence: 99%
“…Because of the focus on cocaine, there has been little research into the properties of the leaf’s other alkaloids. This is disappointing as it is highly likely that the substances act synergistically to produce the effect of coca [35], and more research on the entire leaf is needed [36].…”
Section: Introductionmentioning
confidence: 99%
“…‘Cocaine is a tropane alkaloid that biologically acts as a serotonin-norepinephrine-dopamine reuptake inhibitor’ [36, p.568]. When the potential for addiction was understood, cocaine became illegal in the US in 1914 and its use declined.…”
Section: Introductionmentioning
confidence: 99%
“…Reported benefits include stimulation and rejuvenation, as well as the alleviation of hunger and thirst. 215 It is also commonly used by travelers to South America for the relief of altitude sickness, especially in and around Machu Picchu. 213,215 Cocaine was first isolated by Niemann in 1855, and popularized by Sigmund Freud for its stimulant and euphoric effects in 1884.…”
Section: Cocainementioning
confidence: 99%
“…215 It is also commonly used by travelers to South America for the relief of altitude sickness, especially in and around Machu Picchu. 213,215 Cocaine was first isolated by Niemann in 1855, and popularized by Sigmund Freud for its stimulant and euphoric effects in 1884. 213 Cocaine has many pharmacological roles, including its role as a local anesthetic which was discovered by Carl Koller in 1884.…”
Section: Cocainementioning
confidence: 99%